Study of Welding Dissimilar Metals – Low-carbon Steel AISI 1018 and Austenitic Stainless Steel AISI 304 - Younis K. Khdir; Salim A. Kako; Ramadhan H. Gardi (Polytechnic)
The aim of this study is to investigate the influence of different heat inputs on mechanical properties and microstructure of dissimilar electrical arc welded austenitic stainless steel AISI 304 and lowcarbon steel (CS) joints. The mechanical properties of welded austenitic stainless steel type AISI 304 and low-CS are studied. Five different heat inputs 0.5, 0.9, 1.41, 2, and 2.5 KJ/min were applied to investigate the microstructure of the welded zone and mechanical properties. The results showed that the efficiency of the joints and tensile strength increased with increasing heat inputs, while excess heat input reduces the efficiency. Furthermore, changes in microstructure with excess heat input cause failure at the heat-affected zone.